Antibiotic Treatment Reduces the Health Benefits of Soy Protein. Issue 17 (11th August 2020) - Sánchez‐Tapia, Monica; Moreno‐Vicencio, Daniela; Ordáz‐Nava, Guillermo; Guevara‐Cruz, Martha; Granados‐Portillo, Omar; Vargas‐Castillo, Ariana; Torres, Nimbe; Tovar, Armando R.
Abstract : Scope: Soy protein is a high‐quality protein and its consumption has been associated with a reduction of serum cholesterol and triglycerides and an improvement in insulin resistance. However, it is not known whether the effects of soy protein are mediated by the gut microbiota. Thus, the aim of this study is to assess whether using antibiotics to partially eradicate the gut microbiota can prevent the beneficial effects of soy protein in rats. Methods and results: Thus, rats are fed one of the following diets for 16 weeks: casein control, soy protein control, high‐fat casein, and high‐fat soy protein. The rats are then treated for 4 weeks with antibiotics. Body weight and composition, energy expenditure, glucose tolerance test, metabolic endotoxemia, and gut microbiota are measured before and after treatment with antibiotic. The results show that soy protein consumption decreases weight gain, body fat, metabolic endotoxemia, and increases energy expenditure and glucose tolerance. Antibiotic treatment suppresses all these metabolic effects. These changes are accompanied by modifying the diversity and taxonomy of the gut microbiota. Conclusion: In conclusion, the evidence suggests that the health benefits of soy protein are partly dependent of the gut microbiota. Abstract : The consumption of soy protein produces changes in the gut microbiota associated with a decrease in metabolic endotoxemia, an improvement in insulin sensitivity and an increase in energy expenditure despite consuming a high‐fat diet; however, with the partial elimination of the intestinal microbiota with antibiotics, many of these effects are reduced, suggesting that soy protein effects are in part mediated by the gut microbiota.